Macroeconomic effects of unemployment benefits in small open economies: a stock–flow consistent approach - Mikael Randrup Byrialsen; Hamid Raza (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2018)
This paper attempts to analyse the macroeconomic effects of unemployment benefits in a small open economy. We adopt a stock–flow consistent (SFC) approach with an emphasis on the dynamics of the labour market. We numerically solve the model using a combination of estimation and calibration to generate statistics for our key variables, reflecting features of the Danish economy. We then analyse the effects of a fall in the unemployment compensation rate on the economy. The results indicate that a fall in the compensation rate at a macro level leads to a trade-off between a fall in aggregate demand and a rise in net exports. Due to this trade-off, the net effect of a fall in the compensation rate on the aggregate unemployment rate tends to be weak. Our analyses in this paper raise several questions on the existing views regarding unemployment benefits adopted by a large strand of the economic literature.
Keywords: E24; E12; E60; J20; J30; 330; stock–flow consistent models; labour market; unemployment benefits; macroeconomic outcomes; small open economies